Fuzzy Stochastic Multiobjective Programming - Sakawa, Masatoshi; Nishizaki, Ichiro; Katagiri, Hideki; SpringerLink (Online service) (New York, NY : Springer New York, 2011)
Although studies on multiobjective mathematical programming under uncertainty have been accumulated and several books on multiobjective mathematical programming under uncertainty have been published (e.g., Stancu-Minasian (1984); Slowinski and Teghem (1990); Sakawa (1993); Lai and Hwang (1994); Sakawa (2000)), there seems to be no book which concerns both randomness of events related to environments and fuzziness of human judgments simultaneously in multiobjective decision making problems. In this book, the authors are concerned with introducing the latest advances in the field of multiobjective optimization under both fuzziness and randomness on the basis of the authors$1 (Bcontinuing research works. Special stress is placed on interactive decision making aspects of fuzzy stochastic multiobjective programming for human-centered systems under uncertainty in most realistic situations when dealing with both fuzziness and randomness. Organization of each chapter is briefly summarized as follows: Chapter 2 is devoted to mathematical preliminaries, which will be used throughout the remainder of the book. Starting with basic notions and methods of multiobjective programming, interactive fuzzy multiobjective programming as well as fuzzy multiobjective programming is outlined. In Chapter 3, by considering the imprecision of decision maker$1 (Bs (DM$1 (Bs) judgment for stochastic objective functions and/or constraints in multiobjective problems, fuzzy multiobjective stochastic programming is developed. In Chapter 4, through the consideration of not only the randomness of parameters involved in objective functions and/or constraints but also the experts$1 (Bambiguous understanding of the realized values of the random parameters, multiobjective programming problems with fuzzy random variables are formulated. In Chapter 5, for resolving conflict of decision making problems in hierarchical managerial or public organizations where there exist two DMs who have different priorities in making decisions, two-level programming problems are discussed. Finally, Chapter 6 outlines some future research directions.s
Chapter 1. Introduction and Historical Remarks -- Chapter 2. Fundamentals -- Chapter 3. Fuzzy Multiobjective Stochastic Programming -- Chapter 4. Multiobjective Fuzzy Random Programming -- Chapter 5. Stochastic and Fuzzy Random Two-Level Programming -- Chapter 6. Future Research Directions.
Keywords: Economics; Operations research; Distribution (Probability theory).; Economics/Management Science; Operations Research/Decision Theory; Operations Research, Mathematical Programming; Probability Theory and Stochastic Processes